Analisis Yuridis Penerimaan Peserta Didik Baru (PPDB) Sistem Zonasi Region Di Indonesia: Analisis Yuridis Penerimaan Peserta Didik Baru Sistem Zonasi Region di Indonesia - Tan, Winsherly; Situmeang, Ampuan; Davina Shebiartha, Kyushu (Fakultas Hukum Universitas Jambi, 2024)
Education is a vital human right that must be respected by all Indonesian people. Therefore, fair and equitable education must be provided to all levels of society. However, understanding the concept of